Functional variants in cytochrome b5 type A (CYB5A) are enriched in Southwest American Indian individuals and associate with obesity. Issue 2 (18th January 2022) - Day, Samantha E.; Traurig, Michael; Kumar, Pankaj; Piaggi, Paolo; Koroglu, Cigdem; Kobes, Sayuko; Hanson, Robert L.; Bogardus, Clifton; Baier, Leslie J.
Abstract: Objective: This study aimed to identify genetic variants enriched in Southwest American Indian (SWAI) individuals that associate with BMI. Methods: Whole genome sequencing data ( n = 296) were used to identify potentially functional variants that are common in SWAI individuals (minor allele frequency ≥10%) but rare in other ethnic groups (minor allele frequency < 0.1%). Enriched variants were tested for association with BMI in 5, 870 SWAI individuals. One variant was studied using a luciferase reporter, and haplotypes that included this variant were analyzed for association with various measures of obesity ( n = 917‐5, 870), 24‐hour energy expenditure (24‐h EE; n = 419), and skeletal muscle biopsy expression data ( n = 207). Results: A 5′ untranslated region variant in cytochrome b5 type A ( CYB5A ), rs548402150, met the enrichment criteria and associated with increased BMI ( β = 2%, p = 0.004). Functionally, rs548402150 decreased luciferase expression by 30% ( p = 0.003) and correlated with decreased skeletal muscle CYB5A expression ( β = −0.5 SD, p = 0.0008). Combining rs548402150 with two splicing quantitative trait loci in CYB5A identified a haplotype carried almost exclusively in SWAI individuals that associated with increased BMI ( β = 3%, p = 0.0003) and decreased CYB5A expression, whereas the most common haplotype in all ethnic groups associated with lower BMI and percentage of body fatness, increased 24‐h EE, and increased CYB5A expression. Conclusions: Further studies on the effects of CYB5A on 24‐h EE and BMI may provide insights into obesity‐related physiology.